Long-Life Design and Test Technology of Typical Aircraft Structures - Liu, Jun (Springer Singapore, 2018)
This book addresses anti-fatigue manufacturing, analysis and test verification technologies for typical aircraft structures, including fastening holes, shot peening plates, different types of joints and wing boxes. Offering concrete solutions to practical problems in aircraft engineering, it will benefit researchers and engineers in the fields of Aerospace Technology and Astronautics.